The BOSS for 21st century organizations : behaviors of smart supervisors: thoughts, reflections, insights, and recommendations for those in supervisory, managerial, and executive roles - Mouriño-Ruiz, Edwin (Emerald Publishing Limited, 2025)
The BOSS for 21st Century Organizations is a must-read for seasoned managers and executives, newly appointed leaders, and anyone contemplating a supervisory role. This comprehensive guide is designed to equip leaders with the tools and insights necessary to excel in their positions and foster a Human Intelligent (HI) Workplace. Drawing on nearly four decades of experience in leadership development, the author has conducted numerous workshops and provided executive coaching to countless managers and executives. With firsthand experience as a manager, the author has observed effective and ineffective behaviors, offering invaluable insights into what truly works in leadership. This book features two essential questionnaires that serve as powerful tools for self-assessment and organizational evaluation. Human Intelligent (HI) Workplace Questionnaire: Evaluate your workplace from both an individual and 360-degree perspective to understand what it takes to create an environment that thrives on human intelligence Leadership Behavior Effectiveness (LBE) Questionnaire: Assess your leadership effectiveness and identify areas for improvement to become a more impactful leader. Whether you are an experienced leader looking to refine your skills, a new manager stepping into a challenging role, or someone considering a supervisory position, The BOSS for 21st Century Organizations offers the guidance and tools you need to succeed. Embrace the journey to becoming a better boss and create a workplace where human intelligence and effective leadership drive success.